Delay-Dependent Observers for Uncertain Nonlinear Time-Delay Systems - Dongmei Yan; Youwei Wang; Jiuhong Wei; Dongzhe Li; Lei Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper is concerned with the observer design problem for a class of discrete-time uncertain nonlinear systems with time-varying delay. The nonlinearities are assumed to satisfy global Lipschitz conditions which appear in both the state and measurement equations. The uncertainties are assumed to be time-varying but norm-bounded. Two Luenberger-like observers are proposed. One is delay observer and the other is delay-free observer. The delay observer which has an internal time delay is applicable when the time delay is known. The delay-free observer which does not use delayed information is especially applicable when the time delay is not known explicitly. Delay-dependent conditions for the existences of these two observers are derived based on Lyapunpv functional approach. Based on these conditions, the observer gains are obtained using the cone complementarity linearization algorithm. Finally, a numerical example is given to illustrate the effectiveness of the proposed method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2466